2018
DOI: 10.1111/codi.13888
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative ileus after colorectal cancer surgery

Abstract: Postoperative ileus is a common complication in colorectal surgery. The results of our study suggest at least two surgeon-dependent risk factors, i.e., open approach and opioids in the postoperative period. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 13 publications
3
27
1
1
Order By: Relevance
“…Despite remarkable progress in the field of colorectal surgery, postoperative complications remain a major problem during the course of colorectal cancer treatment . After colorectal surgery, postoperative ileus (POI) occurs at a frequency of 10%‐17%, resulting in longer hospital stays and higher costs . POI is characterized by lack of bowel sounds, delayed passage of flatus and stool, abdominal distension, nausea, vomiting, and pain .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite remarkable progress in the field of colorectal surgery, postoperative complications remain a major problem during the course of colorectal cancer treatment . After colorectal surgery, postoperative ileus (POI) occurs at a frequency of 10%‐17%, resulting in longer hospital stays and higher costs . POI is characterized by lack of bowel sounds, delayed passage of flatus and stool, abdominal distension, nausea, vomiting, and pain .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to open surgery, laparoscopic colorectal surgery is associated with lower incidence of postoperative bowel obstruction . Some studies have reported that body mass index (BMI), which is widely used for the assessment of general obesity, is also a risk factor for POI . However, recent findings suggest that, compared to BMI, visceral obesity (VO) is more strongly associated with complications after colorectal surgery .…”
Section: Introductionmentioning
confidence: 99%
“…We read the study by Rybakov and colleagues in which the authors assess the rate and independent risk factors for postoperative ileus (POI) after colorectal cancer surgery. The results provide evidence of at least two surgeon‐dependent risk factors, i.e.…”
mentioning
confidence: 99%
“…The use of small effective sample sizes reduces the model's power and precision around significant variables. In addition, important variables associated with POI in previous studies, such as preoperative chronic narcotic use and intraoperative adhesions, were missing from the development cohort. However, although not a perfect surrogate, duration of surgery may reflect intraoperative adhesions and operative difficulty.…”
Section: Discussionmentioning
confidence: 99%